(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This paper examines the complex issue of maintenance rights for divorced Muslim women in India. It explores the tension between religious traditions and evolving legal frameworks that shape these rights. The paper begins by highlighting the landmark case of Shah Bano, which established a woman’s right to maintenance under a universally applicable law (Section 125 of the CrPC). However, it also discusses the subsequent Muslim Women (Protection of Rights on Divorce) Act, 1986 (1986 Act), which limited these rights and created a conflict with Section 125. Further analysis delves into the grounds for claiming maintenance, including reasonable cause for leaving the marital home, cruelty, and the father’s responsibility for children.The paper then explores the recent Shamim Bano case, which offered a more expansive interpretation of maintenance rights for Muslim women. This case, along with Danial Latifi v. Union of India, demonstrates the courts’ attempts to reconcile the 1986 Act with broader legal principles. Despite these efforts, challenges remain. The requirement for spousal consent under the 1986 Act significantly restricts access to Section 125.